Peran Literasi Digital dan Finansial untuk Meningkatkan Keberlanjutan UMKM di Desa Kenep, Sukoharjo - Fadhilah, Aan Cahya; Wahyu Putri, Aisyah Yulita; Azizah, Alfina Tri Elsa Nur; Putri, Alivia Malica; Puspita, Annisa Prila; Hafshah, Bunga Elysia (VISA: Journal of Vision and Ideas, 2024)
Financial literacy and digital literacy can promote the development of Small and Medium-Sized Enterprises (SMEs) to support business sustainability. Financial literacy helps SME participants build financial security and monitor income periodically, while digital literacy can support business activities by leveraging technological advancements. Kenep Village is one of the villages located in Sukoharjo Subdistrict, Sukoharjo Regency, which has many SMEs such as rice cakes, batik, and crackers. Most SME participants sell their products directly to customers or accept orders and transactions conducted in cash. The Community Service Program (MBKM) of Universitas Sebelas Maret (UNS) conducted in Kenep Village aims to implement a digital economy such as digital payments (QRIS) and e-commerce to help SME development and others. This program is carried out through several activities such as socialization, training, and mentoring. With these activities, SME participants can use QRIS as an additional non-cash payment option and utilize e-commerce platforms like Shopee to expand their market reach and increase sales. Besides providing convenience for SME participants, the presence of QRIS and e-commerce can also be felt by consumers, thereby enabling the development of existing SMEs in Kenep Village.